Insights into patient preferences for elective surgery during the COVID-19 pandemic: A prospective analysis of 400 patients awaiting arthroplasty. (1st April 2021) - Hotchen, Andrew James; Khan, Saad A.; Khan, Maaz A.; Seah, Matthew; Charface, Zain H.; Khan, Zarif; Khan, Wasim; Kang, Niel; Melton, Joel Thomas Kirk; McCaskie, Andrew W.; McDonnell, Stephen M.
Abstract : Aims: To investigate factors that contribute to patient decisions regarding attendance for arthroplasty during the COVID-19 pandemic. Methods: A postal questionnaire was distributed to patients on the waiting list for hip or knee arthroplasty in a single tertiary centre within the UK. Patient factors that may have influenced the decision to attend for arthroplasty, global quality of life (QoL) (EuroQol five-dimension three-level (EQ-5D-3L)), and joint-specific QoL (Oxford Hip or Knee Score) were assessed. Patients were asked at which 'COVID-alert' level they would be willing to attend an NHS and a "COVID-light" hospital for arthroplasty. Independent predictors were assessed using multivariate logistic regression. Results: Of 540 distributed questionnaires, 400 (74.1%; 236 awaiting hip arthroplasty, 164 awaiting knee arthroplasty) complete responses were received and included. Less than half (48.2%) were willing to attend for hip or knee arthroplasty while a UK COVID-19 epidemic was in circulation (COVID-alert levels 3 to 5). Patients with worse joint-specific QoL had a preference to proceed with surgery at COVID-alert levels 3 to 5 compared to levels 1 and 2 (hip arthroplasty odds ratio (OR) 1.54 (95% confidence interval (CI) 1.45 to 1.63); knee arthroplasty OR 1.16 (1.07 to 1.26)). The odds of patients with worse joint-specific QoL being willing to attend for surgery at COVID-alert levels 3 to 5 increased further if surgery in a private, "COVID-light" hospital was available (hip arthroplasty OR 3.50 (95% CI 3.26 to 3.71); knee arthroplasty OR 1.41 (95% CI 1.29 to 1.53). Conclusion: Patient decisions surrounding elective surgery have been influenced by the global COVID-19 pandemic, highlighting the importance of patient involvement in ensuring optimized provision of elective surgery during these challenging times. Cite this article: Bone Jt Open 2021;2(4):261–270.